Are the young the Others in Croatian media? - An analysis of newspaper articles about violence among the young - Skelin Horvat, Anita (Array, 2011)
The media are an important tool for creating a public opinion and they can influence the creation of laws and policy. Media representation of young people is important because it can influence the picture about them and it can also influence the young themselves. On the other side, young people can be discriminated and treated with suspicion because of specific media picture about them. In this paper we analyse the corpus of newspaper articles about violence among the young in Croatia that recently occurred. Analysing this discourse we try to find out who the participants are and what they pronounce to be the most important questions and issues in connection with the young and violence. We try to found out how the creation of the text is influenced by power relations and other factors which are connected with the media (i.e. public opinion, stereotypes, public panic) and what is the main picture about the young that they create. We also analyse how the language is used and which language and discourse elements (i.e. style, metaphors, and collocations) are used in creating a specific picture of the young in media.